Politik Hukum Persetujuan Majelis Kehormatan Notaris Dalam Memberikan Ijin Pemanggilan Notaris Oleh Penyidik - Iqbal Zaky (Officium Notarium, 2022)
Notary in Granting Permission to Summon a Notary by Investigators. The discussion begins with the legal political basis, then the political legal approval of the Regional Notary Honor Council in granting permission to summon a Notary by the Investigator. Therefore, this study raises the formulation of the problem, namely How is the Legal Politics of the Approval of the Notary Honorary Council in giving permission to summon a Notary by Investigators? This is a normative which the research object being Article 66 paragraph (1) of Law Number 2 of 2014 on the Position of Notary Public and uses secondary legal materials in the form of laws and regulations and legal documents related to the approval of notary summons, obtained by searching the literature. The approach used in this study is the statutory approach and is analyzed by descriptive qualitative method. The results of this study indicate that political aspects appear to be more dominant than legal aspects, the birth of the Notary Honorary Council as an effort to guarantee legal certainty and protection for the profession A notary who is bound by an oath of office to keep the deeds he makes secret.Key Word: Notary Honorary Council, Legal Politics, Notary AbstrakNotaris dalam Memberikan Ijin Pemanggilan Notaris Oleh Penyidik. Pembahasan diawali dengan landasan politik hukum, kemudian politik hukum persetujuan Majelis Kehormatan Notaris Wilayah dalam memberikan ijin pemanggilan Notaris oleh Penyidik. Oleh karena itu penelitian ini mengangkat rumusan masalah Bagaimana Politik Hukum Persetujuan Majelis Kehormatan Notaris dalam memberikan ijin pemanggilan Notaris oleh Penyidik. Penelitian ini bersifat Normatif dengan obyek penelitian Pasal 66 ayat (1) Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris dan menggunakan bahan hukum sekunder berupa peraturan perundang-undangan serta dokumen hukum yang berkaitan dengan persetujuan pemanggilan notaris, didapat dengan penelusuran kepustakaan. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan Perundang-undangan (state approach) dan dianalisa dengan cara deskriptif kualitatif. Hasil dari penelitian ini menunjukkan bahwa aspek politik terlihat lebih dominan dibandingkan aspek hukum, lahirnya Majelis Kehormatan Notaris sebagai upaya menjamin kepastian dan perlindungan hukum bagi profesi notaris yang terikat pada sumpah jabatan untuk merahasiakan akta yang dibuatnya.Kata-kata Kunci: Majelis Kehormatan Notaris, Politik Hukum, Notaris